Advancements in Energy Storage: Exploring the Impact of Graphene Composites - Shahavi, Mohammad Hassan; Ayrilmis, Nadir (Journal of Composites and Compounds, 2023)
Advancements in energy storage technology have made significant progress with the use of graphene composites. Graphene, a two-dimensional carbon material, is known for its excellent electrical conductivity, exceptional mechanical strength, and unique thermal properties, making it a key material for improving the performance of batteries and supercapacitors. Researchers are working to harness these properties to develop more efficient energy storage solutions. These efforts are particularly important in response to the growing global demand for sustainable energy systems, including renewable energy sources and electric vehicles.